Carcass composition evaluation of sheep grazed on Kikuyu grass (Pennisetum clandestinum) in high altitude area of Kenya - Wachira, J.D.; Kamau, C.R.; Chemitei, V.C.C.; Muia, J.K.; Gichuru, W.N. (1990)
A total of 30 mutton sheep, each consisting of 10 red masai, dorper and hampshire down breeds in equal proportions of 5 males and females were delivered to Muguga Meat Research Laboratory in 1981/82 year for a complete carcass composition valuation. Their mean body weight and age were 31.6 kg and 20 months respectively. The sheep were reared on evergreen Kikuyu grass (Pennisetum clandestinum) pastures without any feed supplementation up to slaughter. The sheep were provided with water and mineral lick ad libitum in the evenings when they were brought to night boma. The research animals received the same management, disease control measures and rotational field grazing patterns. The variables considered besides external and internal organs were weights of farm liveweight, empty body weight, hot carcass weight, cold dressed weight and the dissected joints of meat with bone, lean, butcher's bone, fat and visceral organs, digestive organs, rejects (blood, digesta and offals made of gall bladder, empty bladder, genitals and trimmings). The none significant variables (P<0.05) were mostly from external and internal organs consisting of wet skin, head, feet, heart, pericardium, lungs/trachea, liver, spleen, large intestines, blood and offals. The external organs, fat and the breast butcher's bone were none significant. The highly significant variables (p<0.01) consisted of farm live weight; empty body weight hot and cold dressed carcass weights. The significant variables (P<0.05) were wet digesta and gut trimmings. The means of highly significant (P<0.01) and significant (P<0.05) variables generally ranged in order of dorper, hampshire, all males, all females and red masal breed, respectively.